Indirect and direct interactions between grain aphid and parasitoid in the presence of symbiont Regiella insecticola - Yue Man; Delu Li; Minghui Wang; Zuqing Hu; Jean-Luc Gatti; Nicolas Desneux; Peng Han; Chen Luo (CABI Agriculture and Bioscience)
Abstract Background Aphids often harbor bacterial symbionts that confer resistance to biotic and abiotic stress. Previous studies have primarily examined the direct effects of symbiont infection on parasitoid success but less on aphid population dynamics under indirect parasitic situations, for example when exposed to parasitoid wasp odor. Deciphering this type of indirect effect is essential for understanding dynamics of insect ecosystems and communities and to improve IPM success. Methods We generated Sitobion avenae aphid clonal lines that are genetically identical but differ in Regiella insecticola infection. Then, the indirect odor effect of female parasitoid wasp Aphidius gifuensis (Ashmaed), one of its major natural enemies in the fields, was examined on the aphid lines fitness using different parasitoid densities. With these lines we also tested the direct effect of symbiont presence on aphid resistance against different parasitoid densities. Results Our study found fitness costs for the aphid line hosting Regiella, mainly via an increase in the development time and a reduction in population increase rate. Some of these fitness traits were influenced by the indirect exposure to parasitoid wasp odor with a density effect. Presence of the symbiont also reduced A. gifuensis parasitic success, increased the wasp development time and decreased its emergence weight with low effect of the parasitoid density used for parasitism. Conclusions These results showed that aphid population dynamic was mainly affected by the symbiont presence, but not by parasitoid odor. Symbiont presence also protected aphid from parasitism and affected parasitoid offspring weight and hence their future individual fertility and fitness.